Information and Communication Technology Learning in Lower Classes: Case Study at MI Al Amanah Cijapati, Bandung Regency - Putra, Nareswara Arif; Hendar, Hendar; Surya, Candra Mochamad (Yayasan Azka Hafidz Maulana, 2024)
Information and Communication Technology (ICT) learning has an important role in supporting the development of education in today's digital era. This study aims to investigate the implementation and effectiveness of ICT learning in lower grades at MI Al Amanah Cijapati, Bandung Regency. The research method used is a case study, with data collection carried out through observation, interviews, and document analysis. The results of the study indicate that ICT learning at MI Al Amanah Cijapati has integrated various technologies and learning methods that are appropriate to the level of development of students in lower grades. Factors such as the availability of facilities, teacher training, and support from schools and parents have a significant influence on the effectiveness of ICT learning. These findings provide an important contribution to the understanding of the implementation and strategies of ICT learning at the elementary education level, as well as providing input for the development of better educational policies and practices in the future